Effectiveness of community based-collaborative on forest management of the forest programme III in Central Sulawesi. Issue 1 (1st December 2022) - Golar, G; Muis, H; Herman, A; Simorangkir, W S
Abstract: Indonesia is moving quickly to ratify the Paris Agreement as stipulated in Constitution Number 16/2016 as a total commitment and contribution to reducing global carbon emissions. For this action, Indonesia received a cooperation grant, one of which was the Forest Programme (FP) III Sulawesi. FP III aims to contribute to implementing forest conservation and rehabilitation strategies, as a form of adaptation and mitigation of climate change, through support for improving the livelihoods of the rural poor. This program was conducted with multi-stakeholder management in the Lore Lindu landscape. This study attempted to examine the effectiveness of the project on collaborative community-based forest management with an explanatory approach. The results showed that interconnectivity between programs in each PIU had not gone optimally. Although the village facilitators have carried out their job, the indicator results have not followed the community's needs. In addition, the role of FMUs as the holder of the regional authority at the site level has not been directly involved. It has strategic value for the national interest, ensuring that the forest and land rehabilitation program's implementation will be in the right location on the target because FMUs have detailed data and information at the field level.